Widespread admixture blurs population structure and confounds Lake Trout (Salvelinus namaycush) conservation even in the genomic era - Thaïs A. Bernos; Julie Gibelli; Sozos Michaelides; Hari Won; Hyung-Bae Jeon; Kia Marin; David A. Boguski; Muhammad Yamin Janjua; Colin P. Gallagher; Kimberly L. Howland; Dylan J. Fraser (Scientific Reports)
Abstract Intraspecific variation is important for species’ long-term persistence in changing environments. Conservation strategies targeting intraspecific variation often rely on the identification of management or policy units below the species level based on biological differences among populations. To identify management units, this paper examines intraspecific divergence of Lake Trout (Salvelinus namaycush) in Great Slave Lake (GSL), Canada, using low-coverage whole-genome sequencing data. Specifically, we evaluate genetic differentiation and assess the relationship with morphological, mitochondrial, and putatively adaptive divergence. We show that at least three and up to five genetically distinct Lake Trout populations co-occur in GSL and exhibit differences in spatial distribution and body size, with signatures of selection. However, admixture was widespread (60% of the fish) and population structure was shallow (average F ST = 0.022). These findings highlight that, even in the era of whole genome sequencing, identifying discrete management units to implement conservation efforts and policy can remain challenging in systems where gene flow among genetically and ecologically distinct populations is ubiquitous. To give more recognition to this complexity, management efforts should also focus on the area where adaptive variation is evident, and evolutionary acts are at play, to better protect species’ resilience and adaptive potential in some natural systems.